HOW TO ESTABLISH AND DEVELOP CORPORATE MANAGEMENT (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Management is the administration or organizations whether they are a business, a nonprofit organization or a government body through business administration, nonprofit management or political science sub-field of public administration respectively. It is the process of managing the resources of businesses, governments and other organizations.